USM IS COMMITTED TOWARDS RAISING THE QUALITY AND STANDARDS OF EXCELLENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 6 September 2016 Universiti Sains Malaysia (USM) remains committed towards maintaining and also raising the quality and excellence in academics, while striving to remain as the nation's Research University.